2012
DOI: 10.1111/j.1365-2966.2012.20852.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the fine-structure constant - new results from VLT/UVES

Abstract: Quasar absorption lines provide a precise test of whether the fine‐structure constant, α, is the same in different places and through cosmological time. We present a new analysis of a large sample of quasar absorption‐line spectra obtained using the Ultraviolet and Visual Echelle Spectrograph (UVES) on the Very Large Telescope (VLT) in Chile. We apply the many‐multiplet method to derive values of Δα/α≡ (αz−α0)/α0 from 154 absorbers, and combine these values with 141 values from previous observations at the Kec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
438
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(479 citation statements)
references
References 65 publications
38
438
3
Order By: Relevance
“…The fitting approach followed that of, e. g., Murphy et al (2003), King et al (2012), and Molaro et al (2013) except that we construct our fits using the blinded spectra (see the description of the blinding procedure in Section 4). The first step in the fitting process was to model the spectra with multiple components for each absorption system.…”
Section: Fitting Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…The fitting approach followed that of, e. g., Murphy et al (2003), King et al (2012), and Molaro et al (2013) except that we construct our fits using the blinded spectra (see the description of the blinding procedure in Section 4). The first step in the fitting process was to model the spectra with multiple components for each absorption system.…”
Section: Fitting Approachmentioning
confidence: 99%
“…When King et al (2012) combined their VLT measurements with the Murphy et al (2004) Keck ones, they found internally consistent evidence for a dipolar variation in α across the sky. In order to have any confidence in this result, we must be assured that the α-dipole is the result of physics varying in different parts of the universe and not the result of systematic errors between observations and/or spectrographs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations